The third-party regulation on food safety in China: A review - Man ZHANG; Hui QIAO; Xu WANG; Ming-zhe PU; Zhi-jun YU; Feng-tian ZHENG (Journal of Integrative Agriculture, 2015)
Stakeholders in the field of food safety management in China can be classified into three categories, government, food producers (farmers and enterprises), and the third-party regulatory bodies. The third-party regulation has experienced rapid development in past twenty years, and recently received considerable attention from consumers and the central government. This paper provides a review about the development, problems and future trend of the third-party regulation on food safety in China. To be specific, five forms of the third-party regulation are assessed, including media exposure, the third-party certification, regulation by consumer associations, social movements promoted by non-governmental organizations (NGOs), and regulation by industry associations. The study concludes that media and consumer associations are the major players in the third-party regulation and are highly repudiated among customers. The food certification industry has developed rapidly, but is now facing crises of confidence among consumers because of its lack of self-regulation. NGOs and industry associations still remain in the early development stages of food safety management, and therefore, are of little importance in current regulatory bodies.